Baicalin suppress the development of polycystic ovary syndrome via regulating the miR-874-3p/FOXO3 and miR-144/FOXO1 axis - Xiaoyuan Xu; Xiaohua Xu; Xiaoshuang Wang; Ling Shen (Taylor & Francis Group, 2023)
AbstractContext Polycystic ovary syndrome (PCOS) is a common and complex disease caused by endocrine and metabolic dysfunction in women of reproductive age. Baicalin is reported to ameliorate PCOS.Objective This study determines whether baicalin could affect the progression of PCOS.Materials and methods To establish an animal model of PCOS, female Sprague-Dawley (SD) rats were subcutaneously injected with dehydroepiandrosterone (DHEA, 60 mg/kg) for 20 days. Next, normal and PCOS mice were divided into 3 groups: control, PCOS, PCOS + Baicalin (20 mg/kg) groups. In addition, the levels of microRNA-874-3p (miR-874-3p) and microRNA-144 (miR-144) in ovarian tissues were assessed by reverse transcription-quantitative polymerase chain reaction (RT-qPCR).Results Compared to the PCOS group, baicalin treatment significantly declined free testosterone (33.71 pg/mL vs. 56.05 pg/mL) and luteinizing hormone (LH; 3971.73 pg/mL vs. 5201.50 pg/mL) levels in rats with PCOS. Additionally, compared to the control group, 100 μM baicalin lessened miR-874-3p and miR-144 levels in human ovarian granulosa cells (KGN cells) by 36.87% and 32.57%, respectively. Furthermore, forkhead box O (FOXO) proteins FOXO1 and FOXO3 are the direct targets of miR-144 and miR-874-3p, respectively. Meanwhile, baicalin induced G0-G1 phase arrest (69.56 ± 3.7% at baicalin with 100 μM vs. 51.24 ± 3.2%, control) in KGN cells correlating with decreased p27 Kip1 (FOXO proteins downstream effector gene) expression by 55.5%; however, miR-874-3p or miR-144 overexpression could abolish this effect.Conclusions Baicalin could alleviate the symptoms of PCOS via regulating miR-874-3p/FOXO3 and miR-144/FOXO1 axis, demonstrating its potential utility in PCOS treatment.